Functional Connectivity Changes Across the Spectrum of Subjective Cognitive Decline, Amnestic Mild Cognitive Impairment and Alzheimer’s Disease - Wang, Ziqi; Qiao, Kaini; Chen, Guanqun; Sui, Danyang; Dong, Hao-Ming; Wang, Yin-Shan; Li, Hui-Jie; Lu, Jie; Zuo, Xi-Nian; Han, Ying (Frontiers in Neuroinformatics, 2019)
The abnormality occurs at molecular, cellular as well as network levels in patients with Alzheimer’s disease (AD) prior to diagnosis. Most previous connectivity studies were conducted at 1 out of 3 (local, meso and global) scales in subjects covering only part of the entire AD spectrum (subjective cognitive decline, SCD; amnestic mild cognitive impairment, aMCI; and then fully manifest AD). Data interpretation within the framework of disease progression is thus difficult. The current study included 3 age- and sex-matched cohorts: SCD (n=32), aMCI (n=37) and fully-established AD (n=30). A group of healthy elderly subjects (n=40) was included as normal control (NC). Network connectivity was examined at the local (degree centrality), meso (subgraph centrality), and global (eigenvector and page-rank centralities) levels. In compared to NC, SCD subjects had isolated decrease of subgraph centrality in primary (somatomotor and visual) networks. aMCI subjects had decreased centralities at all 3 scales in associative (frontoparietal control, dorsal attention, limbic and default) networks. AD subjects had increased centrality at the global scale in all 7 networks. There was a positive association between MoCA scores and DC in the frontoparietal control network in SCD, a negative relationship between MMSE scores and EC in the somatomotor network in AD. These findings suggest that the primary network is impaired as early as in SCD. Impairment in the associative network also starts at the local level at this stage and may contribute to the cognitive decline. As associative network impairment extends from local to meso and global scales in aMCI, compensatory mechanisms in the primary network are activated.